FC3 Changes in nuclear and mitochondrial DNA damage in primary vascular smooth muscle derived cells and tissue. Issue 17 (26th August 2010) - Hurst, L A; Mercer, J R; Bennett, M R
Abstract : Background: All cells accumulate mitochondrial DNA (MtDNA) damage as they age. However, the tolerance of cells to these mutations remains unknown and has recently been implicated in the pathogenesis of cardiovascular disease. Similarly, while both cellular senescence and DNA damage response (DDR) markers (pATM and pH2AX) increase in vascular smooth muscle cells (VSMCs) with increasing disease severity, the effects of cellular ageing on DDR markers are unknown. Methods: We quantified the common MtDNA deletion (4977 bp), previously documented as a sign of plaque instability, using quantitative PCR (qPCR) in human carotid plaques (n=10) or normal carotids (n = 7). DNA damage and DDR were examined in primary VSMCs of young (mean age 23 years) and older (mean age 60 years) patients using the COMET assay and immunocytochemistry for pATM/pH2AX, respectively. Results: The common mitochondrial deletion increased 1.25-fold in the plaques compared with the normal vessels (p=0.04). In addition, sequencing identified a novel 5031 bp deletion variant, also 1.25-fold higher in the plaques. VSMCs from older patients had increased DNA damage on COMET assay (p=<0.0001) and greater abundance of DDR foci (p=<0.0001) than young patients, both basally and after treatment with the hydrogen peroxide analogue t-BHP. Conclusions: MtDNA damage, manifested as both increased levels of the common and a novel MtDNA deletion, increase in atherosclerosis. VSMC ageing is associated with increased nuclear DNA damage and DDR markers, implying that ageing compromises their ability to repair both nuclear and that MtDNA damage may promote premature senescence and atherosclerosis.